Analisis Penyalahgunaan Media Sosial oleh Remaja di Desa Clumprit Kecamatan Pagelaran - Tri Rahma Supradina; Dita Andriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
As we all know, the progress and sophistication of technology is currently very developed, so it is not surprising that many people understand and use technological advances. Not only in the field of transportation, but technological advances are now almost in various fields, such as in the fields of communication, economics, transportation, academics and several other fields. Human life which started from simplicity has now become a life that can be categorized as very modern. In this era of increasingly sophisticated information and communication technology, everything can be solved in practical ways. Information and communication technology is something that is useful for simplifying all aspects of human life. The current world of information seems inseparable from technology. The use of information and communication technology by society makes the world of technology increasingly sophisticated. Based on this research, the researcher formulated the following: 1) What are the causes of social media abuse committed by teenagers in Clumprit village? teenagers in the village of Clumprit?. This research is a type of text study using a sociological approach. Text study is a method within the scope of qualitative research studies which focuses on the analysis or interpretation of written material based on its context. The writing materials that can be used can include problems that occur in society. In this research, the material or object of research is the problem of social media abuse that occurs among teenagers. Based on the research results, it can be seen that most teenagers in Clumprit village use social media for things that are not useful. Apart from that, most teenage boys are affected by the negative impact of the social media they use, such as quite a few teenage boys who smoke at junior high school (SMP) age, or you could say at underage age, are trapped in negative relationships. not very good, often speeding on the road and what happens very often is that these teenagers indirectly make bad jokes about their friends who are a little weak, or you could say they bully their friends which they think is normal, even though If they want to reflect on the bullying they did, this could have a bad impact on their friends.